Physicians, colonial racism, and diaspora in West Africa - Patton, Adell, 1936- (Gainesville : University Press of Florida, 1996)
The practice of African medicine is ancient - the source, in fact, of a great deal of Western medical knowledge from the Middle Ages onward. Until the close of the nineteenth century, African and West Indian physicians were able to work freely to protect the health of Africans and Europeans alike in West Africa.
In 1901, however, when colonialism - and pseudoscientific racism - were in full force, British administrative action brought about an era of restrictions and segregation, a time of the "closed shop," as British middle-class policy makers described it in the 1950s. Even African physicians trained in the United States and the former Soviet Union and Eastern bloc countries were unwelcome in their countries of origin upon their return home
This book discusses the role of African doctors in colonial state and society, the emergence of Africa's modern medical service, and the contribution of African physicians to an understanding of African diseases and their treatment. It also deals with traditional African medicine, beginning in Egypt 3,000 years ago. Historians and social scientists specializing in West African history, and African historians in general - especially those interested in medicine - will find the book essential.
1. African Physicians in Time Perspective -- 2. The Medical Profession in Africa from Ancient Times to 1800 -- 3. The Sierra Leone Nexus -- 4. The Easmon Episode -- 5. Colonial Medical Union and African Reaction -- 6. M.C.F. Easmon: Protectorate Clinician-Scholar -- 7. David Ekundayo Boye-Johnson and the Decolonization Era -- 8. African Physicians: From the Cold War to Perestroika -- Appendix 1: Colonial List of Qualifying Foreign Medical Schools for the Medical Register -- Appendix 2: West Africa's Relations with the Soviet Bloc, July-September 1959 -- Appendix 3: Ghanaian Physicians Trained in the USSR and the Eastern Bloc, 1984 -- Appendix 4: Sierra Leone Doctors Trained in Soviet and Eastern-Bloc Universities, 1984 and 1967-76.
Includes bibliographical references (pages 301-322) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Physicians -- Africa, West -- History; Medicine -- Africa, West -- History; Physicians -- Political activity -- Africa, West; Africa, West -- Race relations; Africa, West; Physicians -- history; Colonialism -- history; Race Relations -- history; Africa, Western; Médecins -- Afrique occidentale -- Histoire; Médecine -- Afrique occidentale -- Histoire; Médecins -- Activité politique -- Afrique occidentale; Afrique occidentale -- Relations raciales; Afrique occidentale; MEDICAL -- History; Medicine; Physicians; Physicians -- Political activity; Race relations; West Africa; Artsen; Koloniale periode; Rassendiscriminatie; West-Afrika.; History